The Meaning of Friendship In Cyberspace: A Phenomenological Study on Covid-19 Survivors Who Are Experiencing Isolation In Yogyakarta - Priambodo, Patera Adwiko (Journal Research of Social Science, Economics, and Management, 2023)
The WHO announced that COVID-19 has emerged as a global pandemic that threatens world health. Besides the implementation of public health protocols as preventive, curative of positive patients through isolation has also created polemics. Isolation is reported to cause psychological problems for survivors, such as loneliness and depression due to limited social contact. One form of constructive social relations that supports psychological well-being in isolated situations is friendship. The absence of restrictions on using cyberspace during isolation provides an opportunity for survivors to stay connected to get friendly support for healing. This phenomenological study aims to review the meaning of virtual friendship by involving three survivors of COVID-19 who undergo isolation in Yogyakarta. The results found that virtual friendship can reduce various problems during isolation. This friendship is interpreted as providing instrumental, informational, and emotional support, and giving rise to a distinctive meaning in the form of awareness of transcendence.